Association of FAS and FAS Ligand Genes Polymorphism and Risk of Systemic Lupus Erythematosus - Bita Moudi; Saeedeh Salimi; Farzaneh Farajian Mashhadi; Mahnaz Sandoughi; Zahra Zakeri (The Scientific World Journal)
FAS/FASL pathway plays a critical role in maintaining peripheral immune tolerance; therefore, the apoptosis genes, Fas and Fas ligand (FasL), could be suitable candidate genes in human SLE susceptibility. Materials and Methods. In this case-control study, 106 SLE patients and 149 sex, age, and ethnicity matched healthy controls were genotyped for the Fas A-670G and FasLC-844T polymorphisms by polymerase chain reaction-restriction fragment length polymorphism method (PCR-RFLP). Results. The frequency of -670AA genotype was significantly higher in SLE patients than control group and the risk of SLE was 2.1-fold greater in subjects with AA genotype (P=0.03). The frequency of -670A allele was significantly higher in SLE patients than in controls too (58% versus 49%, P=0.03). The -844CC genotype frequency was significantly higher in SLE patients than in healthy controls and the risk of SLE was 2.8-fold greater in these subjects (P=0.01). The C allele frequency was significantly higher in patients than in controls (69% versus 49%, P=0.001). Increased SLE risk was observed in individuals with combined effect of Fas-670AA and FasL-844CC genotypes (P=0.001). Conclusion. Fas-670AA and FasL-844CC genotypes were associated with SLE risk, and combined effect of -670AA and -844CC genotypes might increase SLE susceptibility.